N-Acetylcysteine Combined With Dexamethasone Treatment Improves Sudden Sensorineural Hearing Loss and Attenuates Hair Cell Death Caused by ROS Stress - Bai, Xue; Chen, Sen; Xu, Kai; Jin, Yuan; Niu, Xun; Xie, Le; Qiu, Yue; Liu, Xiao-Zhou; Sun, Yu (Frontiers in Cell and Developmental Biology, 2021)
Sudden sensorineural hearing loss (SSNHL) is a common emergency in the world. Increasing evidence of imbalance of oxidant–antioxidant were found in SSNHL patients. Steroids combined with antioxidants may be a potential strategy for the treatment of SSNHL. In cochlear explant experiment, we found that N-acetylcysteine (NAC) combined with dexamethasone can effectively protect hair cells from oxidative stress when they were both at ineffective concentrations alone. A clinic trial was designed to explore whether oral NAC combined with intratympanic dexamethasone (ITD) as a salvage treatment has a better therapeutic effect. 41 patients with SSNHL were randomized to two groups. 23 patients in control group received ITD therapy alone, while 18 patient s in NAC group were treated with oral NAC and ITD. The patients were followed-up on day 1st (initiation of treatment) and day 14th. Overall, there was no statistical difference in final pure-tone threshold average (PTA) improvement between those two groups. However, a significant hearing gain at 8,000 Hz was observed in NAC group. Moreover, the hearing recovery rates of NAC group is much higher than that in control group. These results demonstrated that oral NAC in combination with ITD therapy is a more effective therapy for SSNHL than ITD alone.